Glutathione Redox System in β-Thalassemia/Hb E Patients - Siritanaratkul, Noppadol; Panichkul, Narumol; Charoensakdi, Ratiya; Hatairaktham, Suneerat; Tangjaidee, Thongchai; Kalpravidh, Ruchaneekorn W.; Fucharoen, Suthat (TheScientificWorld, 2013)
β-thalassemia/Hb E is known to cause oxidative stress induced by iron overload. The glutathione system is the major endogenous antioxidant that protects animal cells from oxidative damage. This study aimed to determine the effect of disease state and splenectomy on redox status expressed by whole blood glutathione (GSH)/glutathione disulfide (GSSG) and also to evaluate glutathione-related responses to oxidation in β-thalassemia/Hb E patients. Twenty-seven normal subjects and 25 β-thalassemia/Hb E patients were recruited and blood was collected. The GSH/GSSG ratio, activities of glutathione-related enzymes, hematological parameters, and serum ferritin levels were determined in individuals. Patients had high iron-induced oxidative stress, shown as significantly increased serum ferritin, a decreased GSH/GSSG ratio, and increased activities of glutathione-related enzymes. Splenectomy increased serum ferritin levels and decreased GSH levels concomitant with unchanged glutathione-related enzyme activities. The redox ratio had a positive correlation with hemoglobin levels and negative correlation with levels of serum ferritin. The glutathione system may be the body’s first-line defense used against oxidative stress and to maintain redox homeostasis in thalassemic patients based on the significant correlations between the GSH/GSSH ratio and degree of anemia or body iron stores.